Systematic reviews in health care : a practical guide - Glasziou, Paul, 1954- (Cambridge University Press, 2001)
This practical guide to systematic reviews clearly describes and explains the methods to systematically identify relevant research, appraise its quality, and synthesize the results. As well as illustrative examples, there are exercises for each of the sections. This is essential reading for those interested in synthesizing health care research.